Submandibular gland excision: From external surgery to robotic intraoral and extraoral approaches. (20th April 2020) - Cammaroto, Giovanni; Vicini, Claudio; Montevecchi, Filippo; Bonsembiante, Anna; Meccariello, Giuseppe; Bresciani, Lorenzo; Pelucchi, Stefano; Capaccio, Pasquale
Abstract: Submandibular gland excision is generally performed through a transcervical approach, a safe procedure that, however, carries few neurological, functional and aesthetic drawbacks. Intraoral approach to the submandibular gland has been described many years ago but it has been newly proposed in recent years thanks to endoscope‐assisted and robot‐assisted surgical procedures. The main purpose of intraoral approaches is to avoid cosmetic sequelae and to reduce the risk of marginal nerve injury although the recent introduction of retroauricular, postauricular, facelift and transhairline neck incisions has overcome the need for an alternative to traditional transcervical approach. Different surgical approaches (transoral versus transcervical) to the submandibular gland as well as different type of cutaneous incisions will be illustrated and discussed in the light of advancement of endoscope‐assisted and robot‐assisted procedures.